Pengaruh Current Ratio, Debt to Equity Ratio, dan Total Asset Turnover terhadap Return on Assets pada PT Kalbe Farma Tbk Periode 2010-2024 - Fera, Feti; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of liquidity proxied by Current Ratio (CR), capital structure measured by Debt to Equity Ratio (DER), and activity measured by Total Asset Turnover (TATO) on profitability as measured by Return on Assets (ROA) at PT Kalbe Farma Tbk for the period 2010–2024. This research employs a quantitative method with an associative approach and utilizes secondary data obtained from the company’s official financial statements through the website www.kalbe.co.id. Data analysis was conducted using multiple linear regression supported by classical assumption tests and hypothesis testing (F-test and t-test). The results indicate that simultaneously CR, DER, and TATO have a significant effect on ROA (F = 25.977; Sig = 0.000). Partially, only the activity variable (TATO) has a positive and significant effect on ROA, while liquidity (CR) and capital structure (DER) do not show a significant effect. These findings are expected to provide useful insights for company management in improving financial performance, particularly through optimizing asset management and operational efficiency.